26.8k views
1 vote
-3x + 10y = 11
-8x + 2y = -20

User Shians
by
4.5k points

1 Answer

5 votes

Answer:

(3, 2)

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination
  • Solving systems of equations by graphing

Explanation:

Step 1: Define systems

-3x + 10y = 11

-8x + 2y = -20

Step 2: Rewrite systems

-8x + 2y = -20

  1. Add 8x to both sides: 2y = 8x - 20
  2. Divide 2 on both sides: y = 4x - 10

Step 3: Redefine systems

-3x + 10y = 11

y = 4x - 10

Step 4: Solve for x

Substitution

  1. Substitute in y: -3x + 10(4x - 10) = 11
  2. Distribute 10: -3x + 40x - 100 = 11
  3. Combine like terms: 37x - 100 = 11
  4. Add 100 to both sides: 37x = 111
  5. Divide 37 on both sides: x = 3

Step 5: Solve for y

  1. Define original equation: -3x + 10y = 11
  2. Substitute in x: -3(3) + 10y = 11
  3. Multiply: -9 + 10y = 11
  4. Add 9 to both sides: 10y = 20
  5. Divide 10 on both sides: y = 2

Step 6: Graph system

Check the system.

-3x + 10y = 11 -8x + 2y = -20-example-1
User Andriy Budzinskyy
by
5.1k points